2014
DOI: 10.1177/0192512113507733
|View full text |Cite
|
Sign up to set email alerts
|

Quotas and intersectionality: Ethnicity and gender in candidate selection

Abstract: Gender equality is not fully realised when it is restricted to ethnic majority men and women. This article examines how gender quotas as a form of equality policy affect ethnic minority groups, in particular, the gender balance among ethnic minority candidates for political office. Our analysis focuses on the selection of ethnic minority candidates in Belgium, where legally binding quotas exist, and in the Netherlands, where they do not. Drawing on 23 interviews with central actors in four main parties in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 31 publications
2
66
1
3
Order By: Relevance
“…Reporting from interviews with party officials in Belgium and the Netherlands, Celis et al (2014) explained how young ethnic-minority women end up being recruited in higher numbers than ethnicminority men exactly because parties are trying to solve this 'intersectional puzzle' of fielding candidates with 'diverse' characteristics.…”
Section: The Political Inclusion Of Women and Ethnic Minoritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reporting from interviews with party officials in Belgium and the Netherlands, Celis et al (2014) explained how young ethnic-minority women end up being recruited in higher numbers than ethnicminority men exactly because parties are trying to solve this 'intersectional puzzle' of fielding candidates with 'diverse' characteristics.…”
Section: The Political Inclusion Of Women and Ethnic Minoritiesmentioning
confidence: 99%
“…However, under other circumstances minority-group women have been found to be included in higher numbers than minority-group men, as parties can cash in the 'complementarity bonus' of being able to count someone as both a woman and a minority (Celis et al 2014). Looking at different combinations of quotas, Hughes (2011) found that minority-group women tend to be disadvantaged by single-dimension quotas for women or minorities, but that they are over-represented compared with other women when there are 'tandem' quotas for both women and minorities at the national level.…”
mentioning
confidence: 99%
“…Women's branches usually constitute key nomination organs as well as critical actors in formulating and advocating strategies for improved representation, such as quotas (see, for example, Krook 2009). As previously emphasized by Celis et al (2014), the role of intraparty organization of gender on the one hand and minorities on the other can mediate the impact of affirmative action strategies.…”
Section: Discussion Of Qualitative Resultsmentioning
confidence: 91%
“…A more informal tactic is the pragmatic ''intersectional puzzling'' that occurs in Belgium and the Netherlands as parties seek to increase the diversity of their electoral slates. In these processes, minority women may enjoy a ''complementarity advantage'' because their identity features maximally complement those of incumbents (Celis and Erzeel, 2015;Celis et al, 2014).…”
Section: Intersectional Institutionsmentioning
confidence: 99%